The relationship between body composition and physical performance in adolescent handball players - Vukadinovic Jurišic, M.; Obradovic, A.; Raškovic, B.; Obradovic, J. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Introduction Success in handball is determined by each player's physical performance, body composition, personality attributes, technical-tactical understanding, and mutual contacts (Vuleta et al., 2001; Moss et al., 2015). Certain body composition parameters are important in discriminating between elite and recreational female handball players (Moss et al., 2015). Therefore, the importance of the body composition and physical performance it is necessary to study them integrally. The aim of this study was to analyze the relationship between body composition and physical performance in adolescent female handball players.